The Vocabulary Acquisition Though Nursery Rhymes by Al-Azhar Kindergarten Children - Ghulam Ikhwan Fhadilla; Otong Setiawan Djuharie; Deni Suswanto (Politeknik Negeri Jakarta, 2025)
This research examines English vocabulary acquisition among kindergarten students through nursery rhymes within the Indonesian educational context, integrating psycholinguistic theories including Chomsky's Universal Grammar, Krashen's Input Hypothesis, and Piaget's Cognitive Development Theory. The study addresses two primary questions: (1) What types of vocabulary are acquired by Al-Azhar Kindergarten children through nursery rhymes? (2) How are certain vocabulary types more frequently acquired through nursery rhymes? The research objectives are to identify and categorize vocabulary types acquired and indicate vocabulary acquisition patterns related to children's cognitive development stages. Employing a qualitative approach, this study observed 25 kindergarten students aged 5-7 years from Al-Azhar Syifa Budi Parahyangan Kindergarten, Padalarang, West Bandung, using purposive sampling. Data collection utilized observational protocols, video recordings, and post-test assessments conducted over four weeks, with each week introducing a different nursery rhyme: